1998
DOI: 10.4037/ajcc1998.7.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Design, testing, and results of an outcomes-managed approach to patients requiring prolonged mechanical ventilation

Abstract: BACKGROUND: Outcomes management that uses critical pathways may decrease costs while improving outcomes for patients who require prolonged mechanical ventilation. OBJECTIVE: To study the efficacy of an outcomes-managed approach to weaning patients from prolonged (more than 3 days) mechanical ventilation. METHODS: A method of multidisciplinary care delivery was designed that included an outcomes manager, a care pathway for patients receiving mechanical ventilation, and weaning protocols. Data collection consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Emphasis on ensuring that care was given in accordance with agreed standards and hospital policies has some similarities with the United States (US) model of ‘managed‐care’ where an advanced nurse practitioner is employed within a clinical team to maintain quality of care and control costs (Satinsky 2000). Outcomes‐managed care has resulted in improved clinical and financial outcomes when acute care nurse practitioners manage patients (Burns et al. 1998, Russell et al.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasis on ensuring that care was given in accordance with agreed standards and hospital policies has some similarities with the United States (US) model of ‘managed‐care’ where an advanced nurse practitioner is employed within a clinical team to maintain quality of care and control costs (Satinsky 2000). Outcomes‐managed care has resulted in improved clinical and financial outcomes when acute care nurse practitioners manage patients (Burns et al. 1998, Russell et al.…”
Section: Discussionmentioning
confidence: 99%
“…Jenny and Logan (1994), who originally defined DVWR, undertook qualitative work regarding the weaning experience (Logan and Jenny, 1997), establishing that while patients became engaged in the process of weaning, it was a stressful experience requiring active participation. Advice and evidence around nurse‐led weaning, where nurses initiate weaning processes, can be conflicting and controversial (Kollef et al , 1997; Burns et al , 1998; Crocker, 2002; Blackwood et al , 2004; Gelsthorpe and Crocker, 2004). Rose and Nelson (2006) undertook a literature review into the evidence for nurse‐led weaning and concluded that there was strong evidence for the safe use of nurse‐led (and other allied health professional) ventilatory weaning.…”
Section: Ventilatory Weaningmentioning
confidence: 99%
“…Although other investigators have reported initiation of various weaning algorithms (15)(16)(17), little published information about the details of compliance with such protocols exists. The first step of our approach involved the RCPs' morning assessment using the DS of weaning parameters.…”
Section: Compliance With the Protocolmentioning
confidence: 99%